2021
DOI: 10.5312/wjo.v12.i6.403
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and revision rate of uncemented humeral head resurfacing: Mid-term follow-up study

Abstract: BACKGROUND Glenohumeral osteoarthritis (OA) is a common cause of pain and disability affecting nearly a third of the world’s population over 60 years of age. As in other joints, shoulder arthroplasty appears to be the most effective treatment. The implant design has evolved during time transitioning to shorter humeral stem lengths or even stemless components. AIM To evaluate the medium-term outcome and survival of a cementless humeral head resurfacing (HHR) in a group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Similar results have been shown in a recent long-term study where the overall complication rate was 15.4%, and the two main complications were pain due to glenoid erosion and stiffness [21]. The two reasons for the pain were related to RHHI positioning and overstuffing [17,20,22]. Moreover, pain after an RHHI has been a problem, especially with the Copeland implant, as overstuffing seems to cause pain due to the implant design [22].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar results have been shown in a recent long-term study where the overall complication rate was 15.4%, and the two main complications were pain due to glenoid erosion and stiffness [21]. The two reasons for the pain were related to RHHI positioning and overstuffing [17,20,22]. Moreover, pain after an RHHI has been a problem, especially with the Copeland implant, as overstuffing seems to cause pain due to the implant design [22].…”
Section: Discussionsupporting
confidence: 84%
“…In contrast to those results, Levy et al reported no revision after 4.4 years of follow-up, and Al-Hadithy et al reported a revision rate of 2% after 4.2 years [3,18]. In the mid-term follow-up studies, reported revision rates varied from 16 to 17% [19,20]. In the long-term follow-up studies, Geervliet et al reported a revision rate of 23% at 9 years, and Gadea et al reported a 10-year prosthesis survival of 88.1% [15,21].…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, resurfacing requires shorter operative time, is less invasive, and is less technically demanding compared with anatomic TSA or reverse TSA. 10,11 Lastly, resurfacing leaves the native glenoid intact, which reduces risk of glenoid loosening or failure in young active individuals, which can allow for greater shoulder functional demands. Stemless implant designs may provide an additional advantage of improved outcomes as compared with their stemmed counterparts.…”
Section: Discussionmentioning
confidence: 99%